Memahami Metode Tafsir Al-Qur'an: Pendekatan Tradisional Dan Kontemporer Dalam Memahami Pesan Pesan Ilahi - Umar Al Faruq; Achdam Khoeron; Althof Hussein Qadhafi; Fatihatul Fatihatul Izzah (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This study aims to understand the methods of interpretation of the Qur'an used in traditional and contemporary approaches in understanding the divine messages contained in the Qur'an. This study uses a qualitative research method with a literature study approach. Primary data was obtained from primary sources such as classical interpretations by well-known scholars, while secondary data was obtained from literature relevant to the research topic. This study explores the differences between traditional and contemporary approaches in the method of interpreting the Qur'an. The traditional approach applies interpretation methods such as interpretation bil ma'tsur, ta'wil, and interpretation bi al-ra'yi, which have been used for centuries by prominent scholars. Meanwhile, the contemporary approach involves methods of interpretation that are more contextual, such as linguistic, historical and social approaches. This research identifies the strengths and weaknesses of each approach, as well as their impact on understanding the divine messages written in the Qur'an. The results of this study indicate that the traditional approach provides a deep understanding of the text of the Qur'an and maintains the intellectual heritage of earlier generations. However, this approach also has limitations in dealing with contemporary challenges and changing times. On the other hand, the contemporary approach provides an understanding that is more contextual and relevant to the current social and cultural context, but can pose a challenge in maintaining the continuity of an authentic understanding of the Qur'anic text. This research provides valuable insights for researchers, mufassir, and Al-Qur'an readers in understanding Al-Qur'an exegesis methods used in traditional and contemporary approaches. This research also underscores the importance of engaging in a holistic and comprehensive method of exegesis in understanding the divine messages written in the Qur'an, taking into account the historical, cultural and social context.